Microwave and conventional sintering of manganese-doped alumina: Densification and mechanical Properties / Salem Dhuban - Salem Omar Abdullah, Dhuban (2019)
The effect of manganese as a densification enhancing additive in alumina was studied. Various manganese percentages (0.1, 0.5, and 1.0 wt. %) were added to alumina powder. The mixture was homogenized using wet milling process. Sintering was carried out in conventional furnace and in hybrid multimode microwave furnace. XRD analysis revealed the precipitation of a spinel second phase (MnAl2O4) in manganese-doped samples as a result of manganese limited solubility in the corundum lattice. 0.1 wt. % manganese addition significantly enhanced the densification process, hindered grain growth, and improved hardness of alumina sintered at 1500 °C. At 1500 °C, 97.5 % relative density was obtained for alumina with 0.1 wt. % manganese content, whereas undoped alumina could only achieve 94.2 % relative density. 0.5 and 1.0 wt. % manganese concentrations resulted in abnormal grain growth at high sintering temperature (1600 °C). The study also revealed that microwave sintering was effective in suppressing grain growth of alumina. In addition, the hardness was dependent on the sintered bulk density and that grain coarsening ensued as the density of the sintered alumina exceeded 95% of theoretical.